Real-time diffraction field calculation method for spatial light modulators with pixelated structure [Pikselli Yapiya Sahip Uzamsal Isik Kipleyicileri için Gerçek Zamanli Kirinim Deseni Hesaplama Yöntemi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
Fast calculation of diffraction field from three-dimensional objects should be achieved to obtain three-dimensional holographic television. Furthermore by taking into account the pixellated structure of the display device in diffraction field calculation, we can obtian more successful results. Proposed method not only paves the way to compute diffraction field in real-time but also takes into account the pixellated structure of the display device. Both numerical and optical experiments give similar results. © 2016 IEEE.
Keywords: Fresnel Diffraction Field; Graphical Processing Unit; Look-Up Table; Parallel Processing; Spatial Light Modulator